PKM penerapan alat peraga Meqip dalam pembelajaran Matematika SD - Ahmad Talib; Baso Intang Sappaile; Nurwati Djam’an (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The mathematics substance is abstract, therefore applying a teaching aids namely Meqip become very important, because students will more easily understand the abstract mathematical concept and principles. The Community Partnership Program (PKM) is held at SD Inpres Mangasa, Gowa Regency. The results of PKM activities are: (1) By using Meqip, students are more enthusiastic in learning mathematics, especially on the plane geometry topic because the activity done is not only sitting and listening to the teacher's description, but also other activities such as observing and seeing all objects directly in Meqip teaching aids, conducting gradual exploration, demonstrating the physical objects of teaching aids, which can improve the students' mastery on the plane geometry topic, (2) This PKM implementation activity, shows that the enthusiasm of the teachers to respond the presented material of PKM program has increased. This is indicated by the amount of teachers who ask questions, suggestions and criticisms, as well as providing a solutive view on the application of Meqip teaching aids, and (3) There was a significant increase of teacher's knowledge and understanding regarding the elementary mathematics concepts. Learning mathematics through Meqip teaching aids can improve the insight of mathematics teachers and make them become more creative, while students will be more enthusiastic in learning mathematics, which also can improve the students' mathematics learning outcomes in elementary school.